Do Computer Science Students Differ from Students of Other Fields of Study in Terms of Multiple Intelligences? - Antoni Wilinski; Joanna Olkowicz; Sebastian Agata; Alicja Szostkiewicz; Szymon Guzik; Arkadiusz Wojtak; Paweł Tomkiewicz (Informatics in Education)
This paper presents survey results involving students from three fields of study (computer science, business, and pedagogy), positing that computer science students exhibit distinct patterns in the spectrum of multiple intelligences compared to students in social sciences disciplines. The study involved over 300 students, revealing statistically significant differences, especially in logical-mathematical intelligence, one of the crucial intelligences according to Howard Gardner's theory and is traditionally measured by IQ indices. Statistical analysis confirms the dominance of computer science students in this intelligence. The data on student preferences were collected through self-assessment in an online questionnaire.